Rút gọn
A = \(\sqrt{28-\sqrt{5}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\sqrt{x}\left(3\sqrt{2}-5\sqrt{8}+7\sqrt{18}\right)+28\\ =\sqrt{x}\left(3\sqrt{2}-10\sqrt{2}+21\sqrt{2}\right)+28\\ =\sqrt{x}\cdot14\sqrt{2}+28=14\sqrt{2}\left(\sqrt{x}+\sqrt{2}\right)\)
\(A=\frac{2}{5+\sqrt{7}}+\frac{\sqrt{28}}{2}-2\)
\(A=\frac{2.\left(5-\sqrt{7}\right)}{25-7}+\frac{2\sqrt{7}}{2}-2\)
\(A=\frac{2.\left(5-\sqrt{7}\right)}{18}+\sqrt{7}-2\)
\(A=\frac{5-\sqrt{7}}{9}+\sqrt{7}-2\)
\(A=\frac{5-\sqrt{7}+9\sqrt{7}-18}{9}\)
\(A=\frac{-13+8\sqrt{7}}{9}\)
Vậy \(A=\frac{-13+8\sqrt{7}}{9}\)
\(A=\frac{2}{5+\sqrt{7}}+\frac{\sqrt{28}}{2}-2\)
\(=\frac{2\left(5-\sqrt{7}\right)}{25-7}+\frac{2\sqrt{7}}{2}-2\)
\(=\frac{2\left(5-\sqrt{7}\right)}{18}+\sqrt{7}-2\)
\(=\frac{2\left(5-\sqrt{7}\right)}{2.9}+\sqrt{7}-2=\frac{5-\sqrt{7}}{9}+\sqrt{7}-2\)
\(a,=27-5\sqrt{3x}\\ b,=3\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}+28=14\sqrt{2x}+28\)
`a)(\sqrt{14}-3\sqrt{2})^2+6\sqrt{28}`
`=14-12\sqrt{7}+18+12\sqrt{7}=32`
`b)2\sqrt{20}-3\sqrt{20}+\sqrt{125}`
`=4\sqrt{5}-6\sqrt{5}+5\sqrt{5}`
`=3\sqrt{5}`.
a) \(\left(\sqrt{14}-3\sqrt{2}\right)^2-6\sqrt{28}\)
\(=\left(\sqrt{14}\right)^2-2\cdot\sqrt{14}\cdot3\sqrt{2}+\left(3\sqrt{2}\right)^2+6\sqrt{28}\)
\(=14-6\sqrt{28}+18+6\sqrt{28}\)
\(=14+18\)
\(=32\)
b) \(2\sqrt{20}-3\sqrt{20}+\sqrt{125}\)
\(=2\cdot2\sqrt{5}-3\cdot2\sqrt{5}+5\sqrt{5}\)
\(=4\sqrt{5}-6\sqrt{5}+5\sqrt{5}\)
\(=3\sqrt{5}\)
Biểu thức này không rút gọn được nữa bạn nhé.